Discourses on the sustainability of nuclear energy: a semi-systematic literature review of scientific production - Riasat Muhammad Amir; Ileana Zeler (Discover Sustainability)
Abstract Sustainability has gained paramount importance in contemporary scientific inquiry, particularly in relation to its profound societal implications. Within this context, the energy sector emerges as a pivotal focus area. Nuclear energy, notably, presents itself as a promising avenue within the spectrum of clean and green energy sources, but this claim is not widely accepted. A comprehensive exploration of discourses surrounding the sustainability of nuclear energy remains absent in scientific production. This paper aims to address this gap by identifying and categorizing main themes within discourses on the sustainability of nuclear energy through the scientific production which are peer review articles (papers) published in journals indexed in WOS and Scopus database. A semi-systematic literature review approach was employed, analysing 59 peer-reviewed journal articles in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) checklist. Through thematic analysis five major themes and thirteen sub-themes were identified. These themes included nuclear perception (assessment, implication, and expectation), nuclear energy policy (national, international, regional), nuclear energy acceptance (drivers and barriers), controversial issues (usefulness and feasibility), and sustainability assessment (benefits, opportunities, and safety). The findings underscore the critical importance for future policy and research endeavours to integrate considerations of nuclear energy's sustainability. Moreover, this study provides a comprehensive overview of the discourses surrounding nuclear energy sustainability, offering valuable insights for regulators, policymakers, academics, and practitioners alike. Ultimately, this study contributes to a more informed dialogue surrounding nuclear energy's role in the pursuit of sustainable energy solutions.